Overexpression of both the lactase gene and its transcriptional activator gene greatly enhances lactase production by Kluyveromyces marxianus. (October 2017) - Ren, Zi-Yan; Liu, Guang-Lei; Chi, Zhe; Han, Yao-Zu; Hu, Zhong; Chi, Zhen-Ming
Graphical abstract: The ribbon representation of the secondary structure of the transcription activator (Lac9) and its conserved amino acids (yellow ones) from K. marxianus KM-0 used in this study. Highlights: Both the lactase gene and its transcriptional activator gene were actively expressed. 274.7 U/ml of lactase activity was produced during the fed-batch fermentation. The main trisaccharides were produced from lactose by the lactase. The transformant KM-L9-20 and the lactase had highly potential applications in biotechnology. Abstract: After both a lactase gene (LAC4 ) and its transcriptional activator gene ( LAC9 ) were expressed in Kluyveromyces marxianus KM-69 which was a glucose-derepressed mutant, one transformant called KM-L9-20 grown in an optimized whey medium for lactase production could produce 77.8 ± 4.0 U/ml of lactase activity at a flask level within 36 h. At the same time, expression of the LAC4 gene and its transcriptional activator gene in the transformant KM-L9-20 were also greatly enhanced compared to that of the LAC4 gene and the LAC9 gene in its parent strain K. marxianus KM-69. 157.9 ± 3.2 U/ml of lactase activity was yielded by the transformant KM-L9-20 within 84 h during a batch fermentation while 274.7 ± 4.3 U/ml of lactase activity was produced within 48 h during a fed-batch fermentation. The produced lactase could actively transform lactose into the galacto-oligosaccharides which contained mainly trisaccharides. The optimal conditions for the transgalactosylation reaction were that the lactose concentration, the reaction temperature, pH and the lactase dose were 400 g/l of lactose, 40 °C, 6.5 and 25 U/g of lactose, respectively. Therefore, the transformant KM-L9-20 and the produced lactase had highly potential applications in biotechnology.